Does the Simple View of Writing Explain L2 Writing Development?: A Meta-Analysis. Issue 5 (3rd July 2020) - Graham, Keith M.; Eslami, Zohreh R.
Abstract: This meta-analysis examines how components of the Simple View of Writing contribute to writing development for English second-language (L2) learners. Previous studies examining first-language learners suggest that transcription and ideation may predict writing achievement. In order to investigate whether these components similarly contribute to L2 writing, this study examined effect sizes (correlations) reported in previous literature on the relationship between components of transcription and ideation to writing. After a systematic search and screening, 30 studies with 97 reported effect sizes were included in this study. Three separate meta-analyses were run for transcription (spelling/handwriting), oral language, and vocabulary. Results suggest that, independently, transcription accounted for 31.22%, vocabulary 24.83%, and oral language 15.76% of variation in writing. Further moderator analyses were run to better understand factors contributing to variation between studies. These results suggest that the components of the Simple View of Writing may explain writing variation in L2 writing.